2016
DOI: 10.1371/journal.pone.0163985
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Neutrophils Promotes the Resolution of Pulmonary Inflammation and Fibrosis in Mice Infected with Paracoccidioides brasiliensis

Abstract: Chronic stages of paracoccidioidomycosis (PCM) are characterized by granulomatous lesions which promote the development of pulmonary fibrosis leading to the loss of respiratory function in 50% of patients; in addition, it has been observed that neutrophils predominate during these chronic stages of P. brasiliensis infection. The goal of this study was to evaluate the role of the neutrophil during the chronic stages of experimental pulmonary PCM and during the fibrosis development and tissue repair using a mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 75 publications
4
53
0
4
Order By: Relevance
“…31 Briefly, mice were injected i.p. with 180 μ g of the antibody 2 days prior to injection of EPC/DSPE-PEG/DiR/DiI liposomes.…”
Section: Methodsmentioning
confidence: 99%
“…31 Briefly, mice were injected i.p. with 180 μ g of the antibody 2 days prior to injection of EPC/DSPE-PEG/DiR/DiI liposomes.…”
Section: Methodsmentioning
confidence: 99%
“…This is supported by another murine study that demonstrated that neutrophil‐elastase‐deficient mice present a significant reduction in fibroblast and myofibroblast accumulation in comparison to wild type mice and that elastase deficiency protected mice from asbestos‐induced pulmonary fibrosis (Gregory et al., ). Moreover, a mouse model of pulmonary fibrosis induced by chronic fungal infection with Paracoccidioides brasiliensis showed that depletion of neutrophils could attenuate pulmonary fibrosis and inflammation (Puerta‐Arias, Pino‐Tamayo, Arango, & Gonzalez, ). This suggests that, at least in these models, the pro‐inflammatory activity of neutrophils, possibly through the production of neutrophil elastase and other compounds, can promote tissue injury leading to a continuous activation of myofibroblasts in an attempt to heal the tissue, therefore promoting fibrosis.…”
Section: Myeloid Cells In Tissue Repair and Fibrosis In The Lungmentioning
confidence: 99%
“…All of these depletion strategies have disadvantages and are not applicable during infectious diseases. Antibody administration depletes both MDSCs and their pro‐inflammatory counterparts; in fact, the administration of anti‐Ly6G is a common strategy to induce neutropenia during infectious disease . The same goes for CCR2‐DTR mice.…”
Section: Functional Mdscs Studies: Depletion Strategies and In Vitro mentioning
confidence: 99%